A Comparative Study on Antioxidant and Antibacterial Activities of Four Senecio Species From Turkey - Sevil ALBAYRAK; Ahmet AKSOY; Lutfiye YURTSEVEN; Abit YAŞAR (International Journal of Secondary Metabolite)
The present study was conducted to investigate total phenolic content, antioxidant and antibacterial activity of four Senecio L. (Asteraceae). The in vitro antioxidant activities of extracts were evaluated with different antioxidant testing systems. Their antioxidant activities were assessed by phosphomolybdenum reduction, DPPH and β-carotene bleaching assay. The extracts exhibited strong antioxidant activity and high scavenging activities against DPPH free radicals. While the extracts exhibited weak to moderate β-carotene bleaching activity. The antimicrobial activity of Senecio extracts was tested against 15 microorganisms using agar diffusion and broth microdilution assays. The extracts were found to be weak to moderate effective against 8 out of the 15 microorganisms tested with minimal inhibitory concentration (MIC) values ranging from 1.5 to 12.5 mg/ml. In conclusion, it can be concluded that Senecio extracts may be considered as natural sources in many industry such as food and pharmacy.